Psychometric properties of the Alexian Brother Urge to Self-Injure (ABUSI) Spanish version for adolescents (2023)
Objective: This study aimed to evaluate the psychometric properties of the Alexian Brother Urge to Self-Injure (ABUSI) in its Spanish version for Colombian adolescents. This instrument was created to measure cognitive and emotional aspects of the urge to self-injure by assessing the frequency, the urge, thoughts associated with time and place, the capacity for resistance, and thoughts associated with the urge to self-injure. Method: A total of 752 preadolescents and adolescents between 10 and 18 years of age, with a mean of 15.3 years (SD = 1.97), participated. The instruments used were The Alexian Brother Urge to Self-Injure ABUSI, ERS Suicide Risk Scale, Plutchik Suicide Risk Scale, and the Zimet The MSPSS Perceived Social Support Scale. Confirmatory factor analysis, inter-test correlations, to estimate cut-off point discriminant validity Receiver Operating Characteristics (ROC) and to determine convergent validity, a Pearson’s coincidence analysis was performed between the ABUSI total score and the ERS Suicide Risk Scale, the Plutchik’s Suicide Risk Scale and Zimet’s Perceived Social Support Scale assessments. Results: The presence of a unidimensional model of the instrument is confirmed with adequate fit, reliability, and concurrent validity indices. The high score classification was determined from six (6) points for the total of the scale. These results show that ABUSI is a valid and reliable tool for the clinical assessment of self-injurious behavior in adolescents and preadolescents.